Application of a phase loop system to analysis of a doppler signal in ultrasonic systems - PIECHOCKI, Maciej; XHAARD, Michel; PERONNEAU, Pierre (Archives of Acoustics, 1985)
This paper presents a way of applying a phase loop system to the measurement of the instantaneous frequency of a Doppler signal in ultrasonic systems. This system was used to verify experimentally the dependence proposed by ANGELSEN [1], connecting the instantaneous probability distribution of the signal with its power spectrum. It presents measured results for two, laminar and turbulent, flows, and also an example of the operation of the phase loop system for a signal with a low signal to noise power ratio.